ANALISIS KONTRIBUSI PEREMPUAN DALAM PENGEMBANGAN PENDIDIKAN KARAKTER PADA NOVEL SI ANAK PEMBERANI - Faridatur Riskiyah; Eti Setiawati (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
Women are often seen as an incapable group that does not have more capacity than men, but women are proven to have an important role in the development of character education. A novel as literature is a learning medium to introduce the essential role of women in character development amid the rise of contradictory reading materials containing harmful content contrasting with Pancasila values. This research aimed to examine the implicit values of character development in the novel "Si Anak Pemberani" regarding women's roles. The analysis was conducted using a qualitative research method with a descriptive approach to determine the values shown by female characters in this novel. Data was collected by emphasizing the dominant female characters in values' building and distributions. The collected data had been presented in a table to identify whichever values appealed to specific figures clearly. The results showed that those values consisted of tolerance, curiosity, social care, environmentalism, integrity, responsibility, religiosity, and nationalism. This study practically can be helpful for educators in either formal or non-formal institutions to habit the young generation in reading books containing positive values as a character development method.